Elevation of intact and proteolytic fragments of acute phase proteins constitutes the earliest systemic antiviral response in HIV-1 infection - Kramer, H; Lavender, K; Qin, L; Stacey, A; Liu, M; di Gleria, K; Simmons, A; Gasper-Smith, N; Haynes, B; Mcmichael, A; Borrow, P; Kessler, B (2010)
The earliest immune responses activated in acute human immunodeficiency virus type 1 infection (AHI) exert a critical influence on subsequent virus spread or containment. During this time frame, components of the innate immune system such as macrophages and DCs, NK cells, b-defensins, complement and other anti-microbial factors, which have all been implicated in modulating HIV infection, may play particularly important roles. A proteomics-based screen was performed on a cohort from whom samples were available at time points prior to the earliest positive HIV detection. The ability of selected factors found to be elevated in the plasma during AHI to inhibit HIV-1 replication was analyzed using in vitro PBMC and DC infection models. Analysis of unique plasma donor panels spanning the eclipse and viral expansion phases revealed very early alterations in plasma proteins in AHI. Induction of acute phase protein serum amyloid A (A-SAA) occurred as early as 5-7 days prior to the first detection of plasma viral RNA, considerably prior to any elevation in systemic cytokine levels. Furthermore, a proteolytic fragment of alpha-1-antitrypsin (AAT), termed virus inhibitory peptide (VIRIP), was observed in plasma coincident with viremia. Both A-SAA and VIRIP have anti-viral activity in vitro and quantitation of their plasma levels indicated that circulating concentrations are likely to be within the range of their inhibitory activity. Our results provide evidence for a first wave of host anti-viral defense occurring in the eclipse phase of AHI prior to systemic activation of other immune responses. Insights gained into the mechanism of action of acute-phase reactants and other innate molecules against HIV and how they are induced could be exploited for the future development of more efficient prophylactic vaccine strategies. © 2010 Kramer et al.